Financial system and innovations: Determinants of early stage venture capital in Europe - Christian Schröder (University of Wuppertal, Schumpeter School of Business and Economics, 2009)
This paper highlights the role of financial development in producing innovative products and services. The Venture Capitalists (VCs) plays a crucial role for the realization of product innovation and service innovation. Especially young entrepreneurs face the problem of financial constraints if starting their business and risk capital often is the only option for financing innovative projects. However, the level of early stage venture capital (VC) investments across European countries differs profoundly. Here a panel analysis is employed to identify if technical and innovative opportunities as well as the entrepreneurial environment influence early stage venture capital investments. In addition the role of the financial system to generate or attract early stage VC is emphasized. The empirical analysis covers 15 European countries for the period from 1995 to 2005. The results show that technical and innovation opportunities and the entrepreneurial environment influence the level of early stage risk capital. With respect to the financial system the analysis reveals that a bank based system has a negative impact on the relative amount of early stage VC investments while a market based system generates risk capital for young entrepreneurs. Venture capital and debt provided by banks is found not to be complements but rather substitutes..
urn:nbn:de:hbz:468-20090572
Keywords: G23; 330; Early Stage Venture Capital; Risk Capital; Financial System; Financing Innovations; Risikokapital; Unternehmensgründung; Bankensystem; Finanzmarkt; Finanzsektor; Erfolgsfaktor; EU-Staaten